The Sustainable City: The Characteristic Public Urban Green Space for Enhancing Community Social Sustainability in Baghdad - Sabil, Azmal (International Journal of Sustainable Construction Engineering and Technology, 2021)
United Nations propounded the key to sustainable development, including the Environmental health and social well-being of society. In the city planning and development, public urban green open spaces provide opportunities for social and physical activities among the communities, which can contribute to mental and physical health in improving the social well-being of the community. Iraq is currently suffering from poor social activities, as many open spaces and parks are neglected and deficient. Therefore, there is a need to enhance residentsâ€™ social interaction in public urban green open spaces in order to improve the quality of social fabric in Baghdad City, through the perspective of the sustainable built environment approaches. The aim of this study is to determine the preferred characteristics of pocket parks for enhancing residents’ social interaction based on their socio-demographic and investigate the relationship between the availability of quality pocket parks and residents’ social interaction in Baghdad City. The study employed by executed the survey to the communities in Karkh district. Respondents (n=306) were selected in a single-random procedure to assess population attitudes towards a pocket park for social and physical activities. The results confirmed that a lack of outdoor daily social interaction in Baghdad City due to the inefficient nearby pocket parks. Thus, there is a need for efficient pocket parks designed to be provided. In this study, the characteristics of efficient pocket park design identified as providing suitable activities and elements, accessibility, well-design, proximity, safety and security, administration and maintenance in the pocket park design. This study contributes to the definitions of pocket parks and nearby open spaces by investigating these spaces’ characteristics and benefits towards the social well-being of communities, in achieving the goal of a sustainable community in sustainable city development.